Los difíciles orígenes de la Universidad de Barcelona (1401-1559). - FERNÁNDEZ LUZÓN, ANTONIO (Scripta, 2020)
The first truly university institution in Barcelona was the medical Studium Generale, founded by Martin I in 1401. The next year an arts faculty was added. It was necessary to wait until 1559 for the town hall to reach an agreement with the medical faculty to put into practice the old privilege granted by Alfonso the Magnanimous, who in 1450 founded a Estudio General with all faculties. This university institution, funded and governed by the municipality, quickly became an advanced center of knowledge with a great cultural and political projection in modern Catalonia.